2007
DOI: 10.1021/jm070445z
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Novel Iron Chelators:  Structure−Activity Relationships of the 2-Benzoylpyridine Thiosemicarbazone Series and Their 3-Nitrobenzoyl Analogues as Potent Antitumor Agents

Abstract: Previously, we demonstrated that the potent antiproliferative activity of the di-2-pyridylketone thiosemicarbazone (DpT) series of Fe chelators was due to their ability to induce Fe depletion and form redox-active Fe complexes (Richardson, D. R.; et al. J. Med. Chem. 2006, 49, 6510-6521). We now examine the role of aromatic substituents on the antiproliferative and redox activity of novel DpT analogues, namely, the 2-benzoylpyridine thiosemicarbazone (BpT) and 2-(3-nitrobenzoyl)pyridine thiosemicarbazone (NBpT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

50
392
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(444 citation statements)
references
References 69 publications
50
392
1
Order By: Relevance
“…Among these ligands are 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (Triapine ® ), 74 Tachpyridine, 75 O-Trensox 76 and hybrid chelators derived from pyridoxal isonicotinoyl hydrazone (PIH) 77,78 and thiosemicarbazones. [79][80][81][82][83][84] The success of Fe chelators as potential anti-tumor agents is marked by the entry of Triapine ® into phase I and II clinical trials alone or in combination with a range of chemotherapeutics. 85,86 In fact, recent results with this agent have shown that it can successfully reduce white blood cell counts by 50% in leukemia patients.…”
Section: Iron As Possible Therapeutic Strategy For Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these ligands are 3-aminopyridine-2-carboxaldehyde thiosemicarbazone (Triapine ® ), 74 Tachpyridine, 75 O-Trensox 76 and hybrid chelators derived from pyridoxal isonicotinoyl hydrazone (PIH) 77,78 and thiosemicarbazones. [79][80][81][82][83][84] The success of Fe chelators as potential anti-tumor agents is marked by the entry of Triapine ® into phase I and II clinical trials alone or in combination with a range of chemotherapeutics. 85,86 In fact, recent results with this agent have shown that it can successfully reduce white blood cell counts by 50% in leukemia patients.…”
Section: Iron As Possible Therapeutic Strategy For Cancer Treatmentmentioning
confidence: 99%
“…72,90,91 Studies with 311 and its derivatives 83,92 led to the development of a highly potent series of Fe chelators derived from di-2-pyridylketone thiosemicarbazone (DpT). 59,84,93,94 A number of these ligands have also demonstrated marked in vitro and in vivo anti-tumor activity 82,84,93,94 and are currently being developed as novel anti-cancer agents.…”
Section: Iron As Possible Therapeutic Strategy For Cancer Treatmentmentioning
confidence: 99%
“…Prior studies have shown that pyridine-based molecules are known to possess antiproliferative properties (20,22,30). mTOR is a protein kinase that regulates cell proliferation (18,40).…”
Section: P2281 a Haloacyl Aminopyridine-based Molecule Inhibits Mtomentioning
confidence: 99%
“…The pyridine scaffold is a very common structural motif that can be found in many natural products and in several pharmacologically interesting compounds (20,22,30). Therefore, the synthesis of pyridine derivatives, with the objective of devel-oping new drugs, is an active area of research.…”
mentioning
confidence: 99%
“…The synthesis and characterization of these compounds have been described in detail in previous publications (Yuan et al, 2004;Richardson et al, 2006;Kalinowski et al, 2007;Jansson et al, 2010) and include:…”
mentioning
confidence: 99%